منهج الاعتدال والشورى في نصوص النظام الأساسي للحكم - فاروق عباس محمد, نهاد (revue mofakir; No 13 (2016): مجلـــة المفكــر, 2018)
The nation of middle and moderation is the nation of morals, but any morals , it's the comprehensive civilized ethics that prevail radiance home and abroad , a nation that do not know a racist or prejudiced , nor double standards as occurred in extinct civilizations or even in contemporary recent societies such as South Africa , or as it is now in all Western societies that was exposed by their unethical practices , which was dominated Internalization interface does not reflect the reality of what is behind them . The morals of the people have witnessed a decline and deterioration towards others especially Muslims . Moderation and justice among people are good morals , which were paid focused attention by King Abdul Aziz - God bless him - to build the structure of the state , and the unification of their parts , in order to consolidate the unity, security and stability in the region that was torn by disputes and conflicts and cons Streptococcus and intellectual , with rooting Islamic values and the Islamic approach in social life and state management way and how the state , which emerged from rooting principle of moderation and the Shura Council in the texts of the statutes of the rule in the Kingdom of Saudi Arabia .